THE LEVEL OF AWARENESS ON WASIYYAH: A STUDY AMONG MUSLIM RESIDENTS IN TAMAN MEDAN - Mohd Noor, Nor Adila; Mohamad Awang, Nur Athirah; Ahmad, Md. Yazid; Yahaya, Salimah; Ismail, Che Zuina; Muhammad, Hamizah (Jurnal ’Ulwan, 2023)
Wasiyyah is one of the most crucial concepts to understand before dying. This is necessary to guarantee that beneficiaries receive their rights once a person has died. Therefore, wasiyyah is extremely essential to society and to the testator of wasiyyah itself. In Malaysia, however, people are less concerned about the wasiyyah practice which lead to an increase in frozen asset and unclaimed property. Wasiyyah is an essential aspect of Islamic estate planning that may have an impact on Malaysia’s unclaimed asset statistics. The purpose of this study is to identify the level of awareness of Taman Medan residents on the execution of wills and to investigate the factors influencing the awareness of Muslim residents in Taman Medan toward wasiyyah practice. The research methodologies employed for this study are qualitative and used a random sampling method to interview and collect data from respondents among Taman Medan residents. The qualitative research described in this work sought to investigate the links between wasiyyah practice awareness and independent variables like knowledge, life events, and institutional factors that encourage Muslims in Taman Medan to write wasiyyah. Based on the findings, it shows religion is the most influential element influencing awareness of wasiyyah practice. Hence, the stronger their adherence to religion, the higher their level of awareness of the wasiyyah practice. As a result, the community and ARB as well as responsible parties such as the government, and third parties must work together to address these issues.